Influence of colorant solutions in properties of indirect resin composites - Santos, Daniela Micheline dos [UNESP]; Paula, Adrielle Mendes de [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Ereitas da Silva, Emily Vivianne [UNESP]; Vechiato Filho, Aljomar Jose [UNESP]; Moreno, Amalia; Goiato, Marcelo Coelho [UNESP] (Mosher & Linder, Inc, 2015)
Purpose: To evaluate the influence of colorant solutions on color stability and surface roughness of indirect resin composites submitted to prior immersion in mouthwashes. Methods: Five brands of indirect resin composites were assessed: Adoro, Resilab, Cristobal, Sinfony and Epricord. The specimens were immersed in five different solutions (n=10): four mouthwashes (Listerine, Oral-B, Plax, Periogard) and artificial saliva (control). 60 hours after immersion in mouthwashes, the specimens were exposed to coffee solution. Shade stability and surface roughness were tested by a spectrophotometer and by a profilometer, respectively. A three-way repeated-measures ANOVA was performed. Differences between the values were compared by the Tukey-Kramer test (P< 0.05). Results: The majority of the specimens showed human-perceptible color change. Greater color change was observed after immersion in coffee, except for Cristobal. The color change was even higher for specimens previously immersed in mouthwashes. The Epricord resin showed the lowest roughness value and the Cristobal showed the highest value, regardless of the period. The highest roughness change occurred after immersion in Listerine.